1984
DOI: 10.1038/ki.1984.130
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulation of prostaglandin E2 and 6-keto-F1α, formation by isolated human glomeruli

Abstract: The intrinsic in vitro production of prostaglandins (PGs) E2, F2 alpha, 6-keto-F1 alpha, and thromboxane B2 (TxB2) and the conversion of exogenous substrate to PGs and TxB2 by isolated human glomeruli was demonstrated, 6-keto-PGF1 alpha was the major product. This was observed under basal conditions and following incubation with exogenous substrate. Indomethacin (Indo; 10(-4 M) inhibited the conversion of arachidonic acid to PGs and the release of [1-14C]-labeled products from human glomeruli by about 80%. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

1986
1986
1997
1997

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 17 publications
0
9
1
1
Order By: Relevance
“…3 ' n Ang n has been shown to stimulate PGE2 and 6-keto-PGF la production by isolated human glomeruli. 13 Therefore, the increase in urinary 6-keto-PGF, a after furosemide administration also might be decreased by captopril, although this was not examined in the present study.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…3 ' n Ang n has been shown to stimulate PGE2 and 6-keto-PGF la production by isolated human glomeruli. 13 Therefore, the increase in urinary 6-keto-PGF, a after furosemide administration also might be decreased by captopril, although this was not examined in the present study.…”
Section: Discussioncontrasting
confidence: 37%
“…These observations confirm and extend a previous report by Attallah et al , 6 who suggested that the effect of furosemide on renal PGE2 production is mediated through the action of Ang n. Ang II is reported to stimulate PGE2 synthesis in the kidney," in cultures of renal medullary interstitial cells, 12 and in isolated glomeruli. 13 On the basis of these observations, the observed increment in furosemide-induced renal PGE2 production can be entirely accounted for by the concurrent increase in Ang n . The obliteration of this response by captopril pretreatment provides additional support for this thesis.…”
Section: Discussionmentioning
confidence: 92%
“…Plasma renin activity (PRA) was measured as the generation of ANG I/ml/h with RIA using commercially available reagents (Sorin Biomedica, Saluggia, Italy). Kidneys were removed, and glomeruli were isolated by differential sieving with ice-cold Krebs-Ringer buffer as previously described (23). Purity of the preparations was assessed by light microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…For some experiments, primary culture of rat mesangial cells (MC) were used. MC were isolated from outgrowth of isolated glomeruli obtained from Sprague-Dawley rats by differential sieving as previously described (23). MC stained positive for the Thy-1 antigen, but failed to bind the anti-Factor VIII antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Details of oursystem have been previously described [16]. Similar amounts (200-250 pg of glomerular protein) and almost identical amounts (1,027±9 glomeruli) of glomeruli from control (C) and RRM rats were always incubated in parallel.…”
Section: Hi Vitro Studiesmentioning
confidence: 99%